ANALISIS PENGARUH KEMANFAATAN APLIKASI PENGENALAN JENIS DAN ARTI RAMBU LALU LINTAS DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Riana Safitri (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2020)
Abstract - Abstract - The research "Application Analysis of the Effect of Recognizing the Type and Meaning of Traffic Signs Using Android-Based Augmented Reality Technology" is a study that focuses on the effect of applying the introduction of the types and meanings of traffic signs to see the perception of end users (end users). This perception is described by the relationship between the influence of the application or the understanding of the community. The method used in this study is a quantitative method to measure the relationship or influence after the application with the level of application user satisfaction. To analyze user satisfaction, the application was tested by using an analysis with the correlation product moment formula. Furthermore, it is calculated by t-test. Meanwhile, to see the relationship/effect of user satisfaction in this study, the reliability test using the Alpha Questionnaire method is said to be reliable if it has an alpha coefficient value greater than 0.6. Decision by comparing r11 with rtabe. From this research, it is known that the application has the most influence on the application of the application of the introduction of the type and meaning of traffic signs. While the most influential in testing the hypothesis using Chi Square and for the level of correlation using the Contingency Coefficient C